Populist Skirmishers: Frontrunners of Populist Radical Right in Poland - Zbytniewska, Karolina (2022)
Mainstream parties, like PiS in Poland, have to cater to broad segments of society to sustain broad support. Cultivation of populist radical right ideologies of authoritarianism, traditionalism, religiosity, and nativism—all interlaced with gender as a nemesis and the nation as a deity—takes highly motivated, confrontational politicians who prepare the ground for radical populist ideas to take root in the electorate’s minds, who mobilize voters through radicalization. This article introduces the concept of “populist skirmishers” to the literature on populism, adding this to Cas Mudde’s basket of major mobilizing forces of populism, that is, a populist leader, a social movement, and a political party. Though it might be considered an unnecessary elevation of a profession that perverts the rules of civility in the public sphere, polarizes electorates, and does whatever it takes to derail the project of European integration, I argue that understanding the modus operandi and functions of populist skirmishers is indispensable to furthering our understanding of populism.